탄화온도가 탄화보드의 열전도율 및 전기적 성질에 미치는 영향 - 오승원; Seung Won Oh; 박상범; Sang Bum Park; 김종인; Jong In Kim; 황정우; Jung Woo Hwang (목재공학, 2013)
탄화보드의 실용화를 위한 기초연구로 중밀도섬유판, 파티클보드, 합판 및 물푸레나무 목재를 400∼1,100°C로 탄화하여 탄화온도에 따른 열전도율 및 전기적 성질을 측정하였다. 열전도율은 탄화 파티클보드의 탄화온도가 900°C일 때 0.1326 m/k로 가장 우수하였으며, 전반적으로 탄화보드의 밀도가 클수록 열전도율이 빨랐다. 비저항값은 탄화온도가 높을수록 감소하여 탄화온도 1,000°C 이후에는 거의 도체에 가까운 값을 나타냈다. 높은 전압으로 탄화보드에 전기를 통했을 때 전류와 전력은 증가하였으며 표면온도가 높았다. This study is a basic research for practical applications of carbonized boards, which measured thermal conductivity and electrical properties of carbonized boards manufactured at different carbonization temperature (400∼1,100°C) using a medium density fiberboard, particleboard, plywood and wood (Fraxinus rhynchophylla). The highest value of thermal conductivity was 0.1326 m/k at carbonization temperature of 900°C in the carbonized particleboard. Overall, the higher density of carbonized board, thermal conductivity was faster. As the electrical resistivity decreased with increased carbonization temperature, it was almost close to conductor after carbonization temperature of 1,000°C. When electricity has worked on the carbonized board by high voltage, the current and the electric power increased and surface temperature of carbonized board was high.